The Influence of Green Accounting, Carbon Emission Disclosure and Environmental Performance on Firm Value : (A Case Study of Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period) (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study analyzes the effect of green accounting, carbon emission disclosure, and environmental performance on firm value. The research is motivated by growing awareness of environmental sustainability, climate change concerns, and the demand for corporate transparency and accountability in managing environmental impacts. Firms are expected not only to achieve financial goals but also to actively manage environmental responsibilities to create long-term value for stakeholders. The research sample consists of 64 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023 that meet the purposive sampling criteria and provide complete sustainability and annual reports. A quantitative approach is used with secondary data from annual and sustainability reports. The independent variables are green accounting (X1), carbon emission disclosure (X2), and environmental performance (X3), while the dependent variable is firm value (Y), measured by Tobin’s Q ratio. Multiple linear regression analysis is applied along with classical assumption testing to ensure reliability, followed by partial and simultaneous hypothesis testing. The results indicate that green accounting has no significant effect on firm value, implying that adopting green accounting alone may not influence investor perceptions without broader environmental initiatives. Conversely, carbon emission disclosure and environmental performance have a positive and significant effect on firm value, showing that transparent reporting and measurable environmental improvements can strengthen market confidence. The R² value is 4.4%, suggesting other factors also contribute to firm value. Simultaneously, all three variables significantly affect firm value, highlighting the combined importance of environmental responsibility. The findings provide practical insights for managers, investors, and policymakers: implementing sustainability practices, particularly carbon emission disclosure and improved environmental performance, can enhance investor trust, strengthen corporate reputation, and ultimately increase firm value in the competitive market.